Polish Air Transport Market in the Perspective of the Year 2030 - Ruciński , Andrzej; Madej , Konrad (Studia Oeconomica Posnaniensia, 2016)
The Polish air transport market is a relatively small element of the European and global markets of air transport services. In this paper the conditions for market development are presented. The transport companies and institutions responsible for air transport should focus on Polish air transport market positioning in the healthy competitive environment. The sustainable development efforts should be implemented for the airports' business strategies. Furthermore, the national policy concerning air transport infrastructure development should be coherent with the EU and the domestic transport net development. These are the elements of complete modernization plans leading into the XXI century air transport market model. PLL LOT, the Polish air carrier, should coordinate its development plans with the Star Alliance strategic partner. Besides that, a very important element of the policy will be an effort to define the role of the Warsaw Airport. The effort to incorporate the Central Airport in the Polish transport network is another hot topic. A good strategy will enable the airline to reach 56-70 M passengers by the year 2030. The main purpose of the article is to present the perspectives of the market development until the year 2030. The forecast's time reference point is the year 2008. In the conclusion, it is discussed that the Polish air transport market has strong potential to develop. The highest standards of the modernization efforts, safety, and reliability should be used when building the positive future of the Polish air transport market.